2021
DOI: 10.1038/s41393-021-00644-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of priorities for a Canadian strategy to advance activity-based therapies after spinal cord injury

Abstract: Study Design Participatory design. Objectives Activity-based therapies (ABT) have physical and psychosocial benefits for individuals with spinal cord injury (SCI). A Canadian ABT summit was held to: (1) identify methods used in stroke rehabilitation that may be appropriate for SCI; (2) understand the current state of ABT activities in Canada; and (3) identify priorities for ABT research and care for the next five years. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In 2019 a Canadian ABT Summit brought together a diverse group of stakeholders to create a five-year Canadian ABT Strategy for SCI to advance the evidence and implementation of ABT. 3 Individuals with lived experience, frontline clinicians, healthcare administrators, researchers, funders of SCI/D research, and health policy experts identified key strategic priority areas. Examples of priorities included: identifying current ABT activities across the continuum of care, creating a network to facilitate dialogue across the continuum of care, developing and implementing best practice recommendations for ABT, and studying optimal timing, methods, and dosage of ABT to promote desired outcomes.…”
Section: Canadian Activity-based Therapy Community Of Practicementioning
confidence: 99%
“…In 2019 a Canadian ABT Summit brought together a diverse group of stakeholders to create a five-year Canadian ABT Strategy for SCI to advance the evidence and implementation of ABT. 3 Individuals with lived experience, frontline clinicians, healthcare administrators, researchers, funders of SCI/D research, and health policy experts identified key strategic priority areas. Examples of priorities included: identifying current ABT activities across the continuum of care, creating a network to facilitate dialogue across the continuum of care, developing and implementing best practice recommendations for ABT, and studying optimal timing, methods, and dosage of ABT to promote desired outcomes.…”
Section: Canadian Activity-based Therapy Community Of Practicementioning
confidence: 99%
“…An ABT Summit was held in 2019 to create a Canadian ABT Strategy for SCI/D [ 8 ]. About 40 participants including individuals with lived experience, clinicians, healthcare administrators, researchers and health policy experts attended the meeting.…”
Section: Introductionmentioning
confidence: 99%
“…One of which was to identify current ABT activities across the continuum of care. Part of this priority was to capture a snapshot of current clinical care with regards to equipment use in ABT interventions across Canada for individuals living with SCI/D [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, little is known about the content of SCI/D rehabilitation programs early after SCI/D, in acute care settings. It has been suggested that ABT in the acute care setting could involve preparing patients for ABT later in the continuum of care [ 9 ]. For example, including range of motion exercises to prepare patients physically, or educating patients to prepare them mentally to engage in ABT at a later stage of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%